Microbial Transformations of Nitrogen, Sulfur, and Iron Dictate Vegetation Composition in Wetlands: A Review - Lamers, Leon P.; Van Diggelen, Josepha M.; Op Den Camp, Huub J.; Visser, Eric J.; Lucassen, Esther C.; Vile, Melanie A.; Jetten, Mike S.; Smolders, Alfons J.; Roelofs, Jan G. (Frontiers in Microbiology, 2012)
The majority of studies on rhizospheric interactions focus on pathogens, mycorrhizal symbiosis, or carbon transformations. Although the biogeochemical transformations of N, S, and Fe have profound effects on vegetation, these effects have received far less attention. This review, meant for microbiologists, biogeochemists, and plant scientists includes a call for interdisciplinary research by providing a number of challenging topics for future ecosystem research. Firstly, all three elements are plant nutrients, and microbial activity significantly changes their availability. Secondly, microbial oxidation with oxygen supplied by radial oxygen loss from roots in wetlands causes acidification, while reduction using alternative electron acceptors leads to generation of alkalinity, affecting pH in the rhizosphere, and hence plant composition. Thirdly, reduced species of all three elements may become phytotoxic. In addition, Fe cycling is tightly linked to that of S and P. As water level fluctuations are very common in wetlands, rapid changes in the availability of oxygen and alternative terminal electron acceptors will result in strong changes in the prevalent microbial redox reactions, with significant effects on plant growth. Depending on geological and hydrological settings, these interacting microbial transformations change the conditions and resource availability for plants, which are both strong drivers of vegetation development and composition by changing relative competitive strengths. Conversely, microbial composition is strongly driven by vegetation composition. Therefore, the combination of microbiological and plant ecological knowledge is essential to understand the biogeochemical and biological key factors driving heterogeneity and total (i.e., microorganisms and vegetation) community composition at different spatial and temporal scales.